Indonesia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
Indonesia recovered quickly after being hit hard by contagion from the global financial crisis. Banking fundamentals have improved, with most Indonesian banks reporting high capital, comfortable levels of liquidity, and solid profitability. Banks exhibit rising credit exposures to retail and SMEs. The Crisis Management Protocol functioned well during the crisis, but it has lapsed. A viable capital market will diversify the sources of funding and provide long-term investment opportunities. The small insurance industry should be restructured and gradually expanded to broaden the institutional investor base.